Inclusive Leadership in the Hybrid Work Era: Fostering Employee Well-being and Task Performance through Psychological Safety - Panji Hendrarso; Pryo Handoko; Nina Kurnina; Bambang Dwi Suseno (Annals of Human Resource Management Research, 2025)
Purpose: This study aims to examine the effect of inclusive leadership on employee well-being and task performance, with psychological safety as a mediating variable, in the context of hybrid work among public-sector employees. Methodology: This study employed a quantitative explanatory research design using a survey method. Data were collected from 235 civil servants working in eight districts/cities in Banten Province, Indonesia. A structured questionnaire with a Likert scale was used as the measurement instrument. Data analysis was conducted using partial least squares–structural equation modelling (PLS-SEM) with SmartPLS 4 software. Results: Inclusive leadership had a positive and significant effect on psychological safety, employee well-being, and task performance. Psychological safety significantly affects employee well-being and task performance and partially mediates the relationship between inclusive leadership and both outcome variables. Conclusions: This study is limited by its cross-sectional design, reliance on self-reported data, and focus on public sector employees within a single province. Limitations: This study is limited by its cross-sectional design, reliance on self-reported data, and focus on public sector employees within a single province Contributions: This study contributes to the fields of leadership studies, human resource management, and public administration by extending inclusive leadership theory to hybrid work settings in the public sector and by providing practical insights into leadership development and employee well-being initiatives.